Evaluación de la producción energética de la central eólica Villonaco utilizando modelos numéricos computacionales. - Peña Sotomayor, Luis Alfonso. (2017)
In this paper titling the methodology used and the results obtained from the evaluation of the annual energy production of the wind farm Villonaco using mathematical models used in commercial programs and probabilistic models are presented described. In the first chapter the current situation of renewable energies in Ecuador described, the policies implemented by the Government for change in the energy matrix and a detailed description of the technical characteristics of the wind farm Villonaco and its current status is done. In chapter two commercial programs Meteodyn WT and WAsP are presented, which are used to model wind sites and determine among other things the annual energy production of the park their strengths are detailed and indicate which input parameters for modeling are. In chapter three, the procedure for estimation of energy production from distribution functions Weibull probability and Rayleigh described. In chapter four the results are presented and analyzed the differences obtained with respect to real output value of the park. Finally conclusions and recommendations are presented.